The Paradox of High Transaction Costs in Islamic Banks: Indonesian Regulations and Policies - Budi Sukardi (Journal of Islamic Economics Perspectives, 2026)
Despite functioning on ideals of fairness and risk-sharing, Indonesian Islamic banks suffer a paradox: high transaction costs. This problem stems from operational inefficiencies, as seen by high BOPO and OER ratios, regulatory fragmentation within the dual banking system, and coordination difficulties among supervisory bodies. Previous studies have focused on the financial performance factor in a limited way but have yet to combine regulatory policy analysis with operational efficiency within a complete framework. The purpose of this research is to examine the influence of regulatory inconsistencies and banking policies on the high transaction costs of Indonesian Islamic banks using a descriptive qualitative technique and a literature review. The findings indicate that the BOPO ratio, which ranges from 89.37% to 94.16%, is the primary cause of the high transaction costs, which are exacerbated by overlapping supervision between the Sharia Supervisory Board, the Bank's Sharia Compliance Directorate, and the Financial Services Authority, resulting in inefficiencies and legal risks. This study helps improve the understanding of how to make Islamic banking more efficient by highlighting the need for better regulations, stronger Sharia governance, and including Maqashid Sharia principles in policies to lower transaction costs and boost the competitiveness of Indonesian Islamic banks.